Effectiveness of trauma-focused treatment for patients with psychosis with and without the dissociative subtype of post-traumatic stress disorder. (October 2016) - van Minnen, Agnes; van der Vleugel, Berber. M.; van den Berg, David. P. G.; de Bont, P. A. J. M.; de Roos, Carlijn; van der Gaag, Mark; de Jongh, A.
Summary: This study presents secondary analyses of a recently published trial in which post-traumatic stress disorder (PTSD) patients with psychosis ( n = 108) underwent 8 sessions of trauma-focused treatment, either prolonged exposure (PE) or eye movement desensitisation and reprocessing (EMDR) therapy. 24.1% fulfilled the criteria for the dissociative subtype, a newly introduced PTSD subtype in DSM-5. Treatment outcome was compared for patients with and without the dissociative subtype of PTSD. Patients with the dissociative subtype of PTSD showed large reductions in clinician-administered PTSD scale (CAPS) score, comparable with patients without the dissociative subtype of PTSD. It is concluded that even in a population with severe mental illness, patients with the dissociative subtype of PTSD do benefit from trauma-focused treatments without a pre-phase of emotion regulation skill training and should not be excluded from these treatments.